Ethnicity and Revolution in Panay - Velmonte, Jose Manuel (Kasarinlan: Philippine Journal of Third World Studies, 2009)
In the war for independence, Filipinos fought the Spaniards, Americans and their fellow Filipinos with almost equal difficulty. When revolutionary president Emilio Aguinaldo sent two expeditionary forces from Luzon to liberate strategic provinces in the Visayas the objective could not be achieved without local resistance. The expeditionary forces met lukewarm, if not hostile, reception from the locals. It did not help that the first of two expedition leaders was inclined to burn down uncooperative communities and that the Visayan elite had other plans for the territory. Having fought the Spaniards without aid from the Luzon government, they found the expeditions intrusive and reacted to them as they would an invasion. They even established a system of government not unlike that of the United States' for the following reasons: one, they wanted to be autonomous from the control of Malolos and two, they wanted freedom to define relations with the United States. The joint revolutionary forces' bungled defense of Iloilo and the fingerpointing that followed hinted the obvious flaws of ethnicity which allow Filipinos to see each other not as countrymen but clansmen. In a war against foreigners, the greater threat lies within the Filipinos themselves.